Digital Media Literacy for the Better Santri: Reconsidering the Power of Internet for the Students of Traditional Pesantren - Rahman, Fazlul (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
Santri in traditional Pesantren had always been blamed for their incapability to handle the negative impacts of the digital media (particularly the Internet). In consequence, there have been strict rule limited even strongly forbid the usage of Internet for the santri in that kind of Pesantren. This issue, from a larger perspective, is an issue of the incapability of the digital natives to effectively use digital technologies. At this point, Palfrey and Gasser reminded us that “there are two possible paths before us—one in which we destroy what is great about the Internet and about how young people use it, and one in which we make smart choices and head toward a bright future in a digital age.” Arguing for the potential power of the Internet for developing capacities of the santri (intellectually, religiously, and mentally), this paper is an effort to walk on the second path by proposing a formula of what I call “DMLfS” (Digital Media Literacy for Santri). A SWOT analysis of the formula leads this paper to conclude that the Internet is considerably important for developing santri’s capacities to face the unstoppable-fast changing media technology. The formula of “DMLfS”, this paper argues, is the one of the best answers to the question of how to create a digitally literate santri.